PROFIL KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA OPERASI HITUNG BILANGAN CACAH BERDASARKAN NEWMAN'S ERROR ANALYSIS DI KELAS III SDN 55/I SRIDADI MUARA BULIAN - Cynthia Negara, Melanie; Yantoro; Faisal Hidayat, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the fact that students still find difficulties in solving word problems involving whole numbers. Based on the results of the Mathematics Daily Test 2 (UH-2) in grade III of SD Negeri 55/I Sridadi, out of 27 students, 13 students (48.1%) obtained scores below the Minimum Completion Criteria (KKM) of 68. These results indicate that almost half of the students have not been able to solve word problems well. This study aims to describe the types of student errors and determine the most dominant error stages based on Newman's Error Analysis (NEA). The study was conducted in the even semester of the 2025/2026 academic year with a quantitative descriptive approach using a survey method. The research subjects were 23 grade III students. Primary data were obtained through written tests consisting of two tests, while secondary data were in the form of teacher interviews and documentation. The results of the study showed that in the first test (addition and subtraction), the percentage of errors was reading 21.74%, comprehension 34.78%, transformation 30.43%, process skill 78.26%, and encoding 78.26%, respectively. In the second test (multiplication and division), the percentage of errors was reading 4.35%, comprehension 47.83%, transformation 47.83%, process skill 65.22%, and encoding 60.87%. The most dominant error stage in both tests was process skill error. These findings indicate that students still have difficulty in carrying out calculation procedures correctly, even though some have been able to read and understand the questions quite well.